(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. La clausola generale di ordine pubblico nei rapporti con l’ordinamento matrimoniale canonico: luci e ombre di un percorso tortuoso e accidentato - 2. Il contenuto del limite nella recente giurisprudenza di legittimità in materia di riconoscimento di sentenze e provvedimenti stranieri - 3. Brevi considerazioni conclusive: ordine pubblico e principi confessionali. ‘International’ public order and so-called ‘concordatarian’ public order: the content of the limit in the light of the recent jurisprudence of legitimacy ABSTRACT: The limit of public order at the entry of judgments and provisions of external legal orders is interpreted by the jurisprudence of legitimacy with an increasingly attentive meaning to the subjective interests of the people involved. Thus, the clause is regressively oriented towards the protection of the internal harmony of the legal order, whilst it is progressively oriented towards guaranteeing the rights of individuals, recognized by the Constitutional Charter and the European Charters. This orientation leads to a subjectivized public order, the operation of which is often left to the availability of the parties.